Planning or Refining an Extension Program - David C. Diehl; Sebastian Galindo-Gonzalez (EDIS)
Whether you are a new or experienced agent, the ability to plan a strong Extension program is critical to your success in Cooperative Extension. This 6-page fact sheet lays out the principles of outcomes-focused planning and provides an overview of the planning cycle. Written by David C. Diehl and Sebastian Galindo-Gonzalez and published by the UF Department of Family Youth and Community Sciences, May 2011.